Pharmacophore Generation and Structure-Based Strategies For Nnrti Development Against HIV-1 Rt (Advances in Applied Biological Research, 2024)
The development of Non-Nucleoside Reverse Transcriptase Inhibitors (NNRTIs)  is critical in combating HIV-1 due to the virus’s high mutation rate and resistance  to current therapies. This study aims to identify potential NNRTIs through  pharmacophore generation and structure-based drug design, focusing on the  interaction of candidate molecules with HIV-1 Reverse Transcriptase (RT). Using  molecular docking, three ligands, ZINC000002416705, ZINC000002416703,  and ZINC000014171386, were analyzed for their binding affinity, inhibition  constants, and interactions with key active site residues. The need for this study  arises from the ongoing challenge of drug resistance in HIV treatment. To  identify and evaluate potential NNRTIs against HIV-1 RT using structure-based  pharmacophore modeling and molecular docking. HIV-1 RT was prepared by  removing non-essential molecules, and ligand structures were retrieved and  optimized. Molecular docking was performed using AutoDock, and interactions  were analyzed using Biovia Discovery Studio. ZINC000002416705 exhibited the  highest binding affinity (-8.66 kcal/mol) with significant hydrophobic interactions,  though it lacked interaction with critical active site residues. ZINC000002416703  showed strong binding (-7.77 kcal/mol) and lower inhibition constant but no  hydrogen bonding. ZINC000014171386, with a binding energy of -7.19 kcal/mol,  directly interacted with key residues Lys101, Val106, and Cys181, demonstrating  a potential as an effective NNRTI. ZINC000014171386 emerged as a promising  NNRTI candidate, with binding characteristics comparable to the standard drug  Nevirapine, warranting further investigation and optimization.
Keywords: HIV-1 RT; Pharmacophore; NNRTI; Molecular docking; Autodock; ZINC000014171386